The IBM PC: The Silicon Story. - Singh, Gurbir (Computer (00189162), 2011)
The longevity of the IBM PC architecture, which has had an enormous impact on the evolution of both personal computers and server systems, can be attributed largely to its backward compatibility with existing software applications.